Repairable super-hydrophobic coating with photothermal effect and preparation method
By grafting octamine on carboxylated carbon nanomaterials and mixing them with epoxy resin, a repairable superhydrophobic coating with photothermal effect is prepared, which solves the problems of cumbersome preparation process, narrow substrate applicability, poor stability and poor repairability in the prior art, and improves multi-basin suitability, chemical/mechanical stability and repairability performance.
Patent Information
- Application Number
- CN202411987732.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
AI Technical Summary
The existing repairable superhydrophobic coating preparation process is complicated, the substrate is narrow in suitability, poor chemical/mechanical stability, and poor repairability performance.
An amide reaction is used to graft octamine on the surface of carboxylated carbon nanomaterials, and mixed with epoxy resin and polyamide-based curing agent. The coating is formed by spraying. After heating curing and cooling crystallization, a repairable superhydrophobic coating with photothermal effect is produced.
Repairable superhydrophobic coatings for a variety of substrates are achieved, with excellent chemical/mechanical stability and repairable properties, which can repair damage to surface chemical and physical structures and greatly extend the service life of the material.
Smart Images

Figure CN119708961A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functionalized super-wetting materials, and in particular to a repairable super-hydrophobic coating with photothermal effect and a preparation method thereof. Background Art
[0002] Superhydrophobic materials have attracted much attention due to their great potential in solving ice coating on high-voltage power transmission equipment, adhesion of marine organisms, pollution from crude oil spills, dust accumulation on solar panels, and fingerprint residue on human-machine interfaces. However, due to the unavoidable physical wear and chemical corrosion during use, traditional superhydrophobic materials are prone to lose their superhydrophobicity, resulting in a significant shortening of their service life, which greatly limits the practical promotion and application of the materials. In response to this, researchers have proposed to construct repairable superhydrophobic materials to promptly rebuild damaged rough structures and replenish lost low-surface energy substances. In addition, improving the chemical durability and mechanical stability of superhydrophobic materials through structural design is also one of the important ways to extend the service life of the materials, which can effectively save material maintenance costs.
[0003] The Chinese invention patent with announcement number CN107459668B discloses replicating the shark skin V-groove structure on the surface of an elastomer and grafting polyacrylamide-polyfluoroalkyl acrylate block copolymer to obtain a repairable super-hydrophobic drag-reducing elastomer film with a static water contact angle of more than 150° and a rolling angle of less than 10°; in addition, the Chinese invention patent with announcement number CN108641421B discloses using octadecylamine to modify graphene oxide, and then forming a coating on the surface of a substrate by spraying, brushing, filtration, dipping and other methods, and obtaining a graphene-based repairable super-hydrophobic material with the characteristics of self-cleaning, corrosion resistance and UV resistance after drying; in addition, the Chinese invention patent with announcement number CN116676002B discloses adopting a double-layer design concept, using micron particles, polymers and polyborosiloxane to form a base coating, and then applying a surface coating formed by nanoparticles and polymers to obtain a repairable super-hydrophobic material with high adhesion and high transmittance.
[0004] However, most repairable superhydrophobic materials can only repair chemical structures, and it is difficult to repair serious microstructural damage caused by external forces such as tape peeling and sandpaper abrasion. Although a small number of superhydrophobic materials with repairable microstructures have been reported, they often have problems such as poor mechanical stability and chemical durability, and their service life is not as good as traditional superhydrophobic materials.
[0005] Common repair methods for repairable superhydrophobic materials include heat, light, electricity, solvents and external force. Superhydrophobic materials with multiple repair methods, especially those that can be repaired using natural conditions such as sunlight, are more promising in practical applications. In addition, it is of great significance to simplify the preparation process of repairable superhydrophobic coatings and make them universal in substrates and more conducive to large-scale production and application. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a repairable super-hydrophobic coating with photothermal effect and a preparation method, so as to solve the problems of the prior art such as complicated preparation process of the repairable super-hydrophobic coating, narrow substrate applicability, poor chemical / mechanical stability, and poor repairability.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is: a method for preparing a repairable super-hydrophobic coating with photothermal effect, comprising the following steps:
[0008] Step S1, using an amide reaction to graft octadecylamine onto the surface of a carboxylated carbon nanomaterial at a high temperature of 150° C. to obtain a modified carbon nanomaterial, wherein the present invention first adds the carbon nanomaterial to a mixed solution of concentrated sulfuric acid and concentrated nitric acid, mixes and heats the mixture under reflux, and then cools, washes, and dries to obtain the carboxylated carbon nanomaterial, then adds the carboxylated carbon nanomaterial and the octadecylamine to a dehydration condensation agent for reaction, and then cools, washes, and dries to obtain the modified carbon nanomaterial;
[0009] Step S2, dissolving 5 to 10 parts of epoxy resin and polyamide curing agent in 100 parts of organic solvent by mass fraction to obtain a mixed solution;
[0010] Step S3, ultrasonically dispersing 2 to 10 parts of modified carbon nanomaterial and 0.15 to 1 part of octadecylamine in 100 parts of an organic solvent by mass fraction to obtain a suspension;
[0011] Step S4, mixing 100 parts of the mixed solution of step S2 and 100 parts of the suspension solution of step S3 by mass fraction, and subjecting the mixture to ultrasonic dispersion treatment for 10 to 20 minutes to form a uniformly dispersed suspension solution;
[0012] Step S5, coating the suspension solution on the surface of the substrate by a spraying process to form a coating on the surface of the substrate;
[0013] Step S6, placing the substrate in an oven at a temperature of 60 to 100° C., heating and curing the coating coated on the surface of the substrate, taking the substrate out of the oven and placing it at room temperature, allowing the coating coated on the surface of the substrate to cool and crystallize, and forming a repairable super-hydrophobic coating with a photothermal effect on the surface of the substrate;
[0014] Part of the octadecylamine in the repairable super-hydrophobic coating is grafted to the surface of the carbon nanomaterial, and part of the waxy octadecylamine is directly added to the epoxy resin cross-linking system. The combination of octadecylamine molecules with restricted mobility and octadecylamine molecules with large mobility is utilized to make the repairable super-hydrophobic coating have excellent cyclic repair stability. The repairable super-hydrophobic coating has excellent chemical / mechanical stability and repairability.
[0015] In a further technical solution, the surface of the repairable super-hydrophobic coating has a super-hydrophobic micro-nano rough structure, the modified carbon nanomaterial is accumulated on the surface of the repairable super-hydrophobic coating to construct a micron-sized papillary structure in the shape of a peak, and a large number of nano-sized carbon nanoparticle protrusions are distributed on the surface of the papillary structure, and the mobile octadecylamine molecules with poor stability are restricted in the epoxy resin cross-linking system. After the micro-nano rough structure on the surface of the repairable super-hydrophobic coating is damaged, the waxy octadecylamine is melted and flowed by heating and re-cooled and crystallized in the damaged area to construct roughness;
[0016] After the chemical structure of the surface of the repairable super-hydrophobic coating is damaged, heating is used to accelerate the migration and rearrangement of the octadecylamine chain segments therein to reduce the surface energy of the damaged area, thereby repairing the super-hydrophobicity of the repairable super-hydrophobic coating.
[0017] In a further technical solution, in step S1, a dehydration condensation agent is used in the amide reaction to graft octadecylamine onto the surface of the carboxylated carbon nanomaterial, and the dehydration condensation agent is selected from N,N-dicyclohexylcarbodiimide.
[0018] In a further technical solution, in step S1, the carboxylated carbon nanomaterial is one of carboxylated carbon nanotubes and carboxylated carbon black, wherein the outer diameter of the carboxylated carbon nanotubes is greater than 20 nm, and the particle size of the carboxylated carbon black is distributed in the range of 30 to 500 nm.
[0019] In a further technical solution, in step S2, the epoxy resin selected is of type E-44 or E-51; and the organic solvent is one of ethanol, toluene and tetrahydrofuran.
[0020] In a further technical solution, the mass ratio of the epoxy resin to the polyamide curing agent is 1 to 2:1, the total mass of the epoxy resin and the polyamide curing agent is set to A, the input mass of the carboxylated carbon nanomaterial is 40 to 100 wt% of A, and the input mass of the octadecylamine is 3 to 10 wt% of A.
[0021] In a further technical solution, in step S6, the coating coated on the surface of the substrate is heated and cured for 1 to 10 hours, and the coating is cooled and crystallized for 1 to 6 hours.
[0022] In a further technical solution, in step S5, the substrate comprises one of glass, iron sheet, polyethylene terephthalate film, polypropylene film and polyethylene film, and the thickness of the spray layer of the suspension solution coated on the substrate is 50 to 200 μm.
[0023] A repairable super-hydrophobic coating with photothermal effect is prepared using the above-mentioned method for preparing a repairable super-hydrophobic coating with photothermal effect. Part of the octadecylamine in the repairable super-hydrophobic coating is grafted onto the surface of the carbon nanomaterial, and part of the waxy octadecylamine is directly added to the epoxy resin cross-linking system. The combination of octadecylamine molecules with restricted mobility and octadecylamine molecules with large mobility is utilized to make the repairable super-hydrophobic coating have excellent cyclic repair stability. The repairable super-hydrophobic coating has the chemical / mechanical stability and surface repairability of the material.
[0024] In a further technical solution, the surface of the repairable super-hydrophobic coating has a super-hydrophobic micro-nano rough structure, and a micron-scale papillary structure in the shape of a mountain is constructed by accumulating modified carbon nanomaterials on the surface of the repairable super-hydrophobic coating, and a large number of nano-scale carbon nanoparticle protrusions are distributed on the surface of the papillary structure; the service life of the material is greatly extended by the mobile octadecylamine molecules confined in the epoxy resin cross-linking system, and its excellent photothermal properties are used to provide an effective way for repairability; after the micro-nano rough structure on the surface of the repairable super-hydrophobic coating is damaged, the octadecylamine is melted and flowed by heating and re-cooled and crystallized in the damaged area to construct roughness; after the chemical structure of the surface of the repairable super-hydrophobic coating is damaged, the migration and rearrangement of the octadecylamine segments are accelerated by heating to reduce the surface energy of the damaged area, so as to achieve the repair of the super-hydrophobicity of the repairable super-hydrophobic coating.
[0025] The advantages of the present invention over the prior art are as follows: the present invention solves the problems of the prior art such as complicated preparation process of the repairable super-hydrophobic coating, narrow substrate applicability, poor chemical / mechanical stability, and poor repairability. The prepared repairable super-hydrophobic coating is suitable for substrates of various different materials, and has excellent photothermal conversion performance and chemical / mechanical stability. It can simultaneously repair damage to the surface chemical structure and physical structure, greatly extending the service life of the material, and its excellent photothermal performance provides an effective way for repairability.
[0026] The present invention first grafts octadecylamine onto the surface of a carboxylated carbon nanomaterial, then ultrasonically mixes the material with an epoxy resin, a polyamide curing agent, octadecylamine and an organic solvent, and applies the obtained uniform dispersion to a substrate by a spray coating technique. After heating curing and cooling crystallization, a repairable super-hydrophobic coating with a photothermal effect is obtained. The obtained repairable super-hydrophobic coating confines the relatively unstable and movable waxy octadecylamine molecules within the epoxy resin cross-linking system, and the repairable super-hydrophobic coating as a whole still exhibits excellent chemical and mechanical stability.
[0027] The present invention further simplifies the process, the preparation process is simpler and easy to implement in mass production, and the production cost is further reduced. It can also be applied to a variety of substrates, suitable for industrial production and popularization and application. The prepared repairable super-hydrophobic coating has excellent chemical / mechanical stability and repairability.
[0028] The present invention introduces waxy octadecylamine molecules into the coating, utilizes its melt flow and migration, and cooling recrystallization to rebuild the rough structure on the damaged surface and supplement low surface energy substances, thereby giving the super-hydrophobic material chemical and mechanical repairability. Part of the octadecylamine in the repairable super-hydrophobic coating is grafted onto the surface of the carbon nanomaterial, and part of the octadecylamine is directly added to the epoxy resin cross-linking system. The combination of the octadecylamine molecules with restricted flow and the octadecylamine molecules with a large flow amplitude is utilized to make the repairable super-hydrophobic coating have excellent cyclic repair stability.
[0029] The present invention introduces carbon nanomaterials to enable the super-hydrophobic coating to heat up rapidly under simulated sunlight, and the surface temperature can reach 89°C, providing two repair pathways for the repairable performance of the repairable super-hydrophobic coating. When the repairable super-hydrophobic coating is physically damaged by tape stripping and sandpaper abrasion, the surface roughness structure is damaged, and the octadecylamine of the waxy substance is melted and flowed by heating and re-cooled and crystallized in the damaged area to construct roughness, thereby restoring the super-hydrophobic performance. At the same time, when the repairable super-hydrophobic coating is chemically damaged by plasma treatment, the low surface energy substances on the surface are degraded, and heating can accelerate the migration and rearrangement of the octadecylamine segments therein, thereby reducing the surface energy and repairing the super-hydrophobicity. In addition, the embedding of carbon nanomaterials enables the repairable super-hydrophobic coating to exhibit excellent photothermal effect, and it quickly heats up under simulated sunlight and near-infrared light, which can promote the realization of the repair performance of the repairable super-hydrophobic coating and show extremely high value in practical applications. The present invention uses an epoxy resin cross-linking system to limit the large-scale movement of octadecylamine molecules with poor stability, so that the repairable super-hydrophobic coating has repairability while still showing excellent chemical durability and mechanical stability as a whole, and can effectively resist chemical and mechanical damage such as solvent immersion and tape stripping. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Scanning electron microscope images of the repairable super-hydrophobic coating with photothermal effect prepared in Example 1, with magnifications of 100 times, 1000 times and 10000 times from left to right respectively.
[0031] Figure 2 The surface temperature of the repairable super-hydrophobic coating with photothermal effect prepared in Example 1 changes with the solar radiation time.
[0032] Figure 3Scanning electron microscope images of the repairable super-hydrophobic coating with photothermal effect prepared in Example 1 after being damaged by sandpaper abrasion and repaired by heating, with the magnifications from left to right being 500 times and 10,000 times respectively. DETAILED DESCRIPTION
[0033] Example 1
[0034] First, octadecylamine was grafted onto the surface of carboxylated carbon nanotubes at a high temperature of 150°C by amide reaction to obtain a modified carbon nanomaterial, and the dehydration condensation agent used in the amide reaction was N,N-dicyclohexylcarbodiimide; then, 4.5g E-44 epoxy resin and 4.5g polyamide curing agent were dissolved in 100g tetrahydrofuran to obtain a mixed solution, and then 9g modified carbon nanotubes and 0.47g octadecylamine were ultrasonically dispersed in 100g tetrahydrofuran to obtain a suspension; then, the above suspension and the mixed solution were mixed, and after ultrasonic dispersion treatment for 15min, a uniformly dispersed suspension solution was formed, and the suspension solution was coated on a glass sheet by a spraying process, and the glass sheet was used as a substrate to form a coating on the surface of the glass sheet; finally, it was placed in an oven at 80°C for heating and curing for 2h, and then it was taken out and placed at room temperature for cooling and crystallization for 4h to obtain a repairable super-hydrophobic coating with a photothermal effect, and the repairable super-hydrophobic coating was firmly attached to the surface of the glass sheet.
[0035] Figure 1 Scanning electron microscope image of the photothermal repairable super-hydrophobic coating prepared in Example 1. It can be seen that the modified carbon nanotubes are accumulated on the surface of the repairable super-hydrophobic coating to form a large number of micron-sized papillary structures in the shape of peaks, and the papillary surface is distributed with a large number of nano-sized carbon nanotube protrusions, and the repairable super-hydrophobic coating surface is obviously covered with a thin layer of octadecylamine waxy substance. By combining the micro-nano rough structure and the octadecylamine molecules with low surface energy, the repairable super-hydrophobic coating achieves super-hydrophobic performance, and the surface contact angle reaches 154°. In addition, the repairable super-hydrophobic coating limits the octadecylamine molecules with poor stability and mechanical properties to the epoxy resin cross-linking system, so that the repairable super-hydrophobic coating shows good solvent stability and stripping resistance. The repairable super-hydrophobic coating still maintains super-hydrophobicity after being soaked in n-hexane for 72h, and the contact angle is 152°. At the same time, the repairable super-hydrophobic coating is damaged by tape stripping for 500 cycles, and the contact angle remains at 151°.
[0036] Figure 2The surface temperature of the photothermal repairable super-hydrophobic coating prepared in Example 1 changes with the simulated solar irradiation time. It can be seen that the repairable super-hydrophobic coating quickly heats up within 5 minutes of irradiation, and the surface temperature rises to 85°C after 5 minutes, and then slowly heats up, and the surface temperature rises to 89°C after 10 minutes. This shows that the modified carbon nanotubes can effectively absorb and capture light under sunlight irradiation, and convert light into heat, and the heat is then quickly transferred to the surface of the repairable super-hydrophobic coating through the highly thermally conductive carbon nanotubes.
[0037] Figure 3 The photothermal repairable super hydrophobic coating prepared in Example 1 is a scanning electron microscope image after sandpaper abrasion damage and heating repair. It can be seen that after repeated sandpaper polishing of the repairable super hydrophobic coating, the surface roughness is greatly reduced, the nanoscale roughness constructed by carbon nanotubes disappears, and the surface contact angle is reduced to 147 °. After heating, the repairable super hydrophobic coating is heated, and the internal octadecylamine is melted and flows, and then migrates to the repairable super hydrophobic coating surface. This process promotes the overall movement of the flat surface, and the repairable super hydrophobic coating restores the undulating rough structure and exposes nano-scale particle protrusions; At the same time, the waxy hydrophobic substance of octadecylamine on the surface increases, and it is crystallized again on the surface after cooling to form roughness, and the two work together to promote the repairable super hydrophobic coating to restore super hydrophobicity, and the contact angle increases to 155 °.
[0038] The test results of the hydrophobicity, solvent stability and peeling resistance of the repairable super-hydrophobic coating are shown in Table 1, and the test results of the photothermal conversion performance and contact angle repair performance of the repairable super-hydrophobic coating are shown in Table 2.
[0039] Example 2
[0040] Firstly, octadecylamine was grafted onto the surface of carboxylated carbon black at a high temperature of 150°C by amide reaction to obtain a modified carbon nanomaterial, and the dehydration condensation agent used in the amide reaction was N,N-dicyclohexylcarbodiimide; subsequently, 3.3 g of E-51 epoxy resin and 1.7 g of polyamide curing agent were dissolved in 100 g of toluene to obtain a mixed solution, and then 2 g of modified carbon black and 0.15 g of octadecylamine were ultrasonically dispersed in 100 g of toluene to obtain a suspension; then, the above suspension and the mixed solution were mixed, ultrasonically dispersed for 10 minutes to form a uniform suspension solution, and then the suspension solution was coated on an iron sheet by a spraying process, and the iron sheet was used as a substrate to form a coating on the surface of the iron sheet; finally, the coating was placed in a 60°C oven for heating and curing for 10 hours, and then it was taken out and placed at room temperature for cooling and crystallization for 6 hours to obtain a repairable super-hydrophobic coating with a photothermal effect, and the repairable super-hydrophobic coating was firmly attached to the surface of the iron sheet.
[0041] The test results of the hydrophobicity, solvent stability and peeling resistance of the repairable super-hydrophobic coating are shown in Table 1, and the test results of the photothermal conversion performance and contact angle repair performance of the repairable super-hydrophobic coating are shown in Table 2.
[0042] Example 3
[0043] Firstly, octadecylamine was grafted onto the surface of carboxylated carbon black at a high temperature of 150°C by amide reaction to obtain a modified carbon nanomaterial, and the dehydration condensation agent used in the amide reaction was N,N-dicyclohexylcarbodiimide; then, 6g E-44 epoxy resin and 4g polyamide curing agent were dissolved in 100g ethanol to obtain a mixed solution, and then 10g modified carbon black and 1g octadecylamine were ultrasonically dispersed in 100g ethanol to obtain a suspension; then, the above suspension and the mixed solution were mixed, ultrasonically dispersed for 20min to form a uniform suspension solution, and then the suspension solution was coated on a polyethylene sheet by a spraying process, and the polyethylene sheet was used as a substrate to form a coating on the surface of the polyethylene sheet; finally, the coating was placed in a 100°C oven for heating and curing for 1h, and then it was taken out and placed at room temperature for cooling and crystallization for 1h to obtain a repairable super-hydrophobic coating with a photothermal effect, and the repairable super-hydrophobic coating was firmly attached to the surface of the polyethylene sheet.
[0044] The test results of the hydrophobicity, solvent stability and peeling resistance of the repairable super-hydrophobic coating are shown in Table 1, and the test results of the photothermal conversion performance and contact angle repair performance of the repairable super-hydrophobic coating are shown in Table 2.
[0045] Example 4
[0046] First, octadecylamine was grafted onto the surface of carboxylated carbon nanotubes at a high temperature of 150°C by amide reaction to obtain a modified carbon nanomaterial, and the dehydration condensation agent used in the amide reaction was N,N-dicyclohexylcarbodiimide; then, 3.5g E-44 epoxy resin and 3.5g polyamide curing agent were dissolved in 100g tetrahydrofuran to obtain a mixed solution, and then 5.25g modified carbon nanotubes and 0.5g octadecylamine were ultrasonically dispersed in 100g tetrahydrofuran to obtain a suspension; then, the above suspension and the mixed solution were mixed, ultrasonically dispersed for 15min to form a uniform suspension solution, and then the suspension solution was coated on a glass sheet by a spraying process, and the glass sheet was used as a substrate to form a coating on the surface of the glass sheet; finally, the coating was placed in an oven at 80°C for heating and curing for 2h, and then it was taken out and placed at room temperature for cooling and crystallization for 2h to obtain a repairable super-hydrophobic coating with a photothermal effect, and the repairable super-hydrophobic coating was firmly attached to the surface of the glass sheet.
[0047] The test results of the hydrophobicity, solvent stability and peeling resistance of the repairable super-hydrophobic coating are shown in Table 1, and the test results of the photothermal conversion performance and contact angle repair performance of the repairable super-hydrophobic coating are shown in Table 2.
[0048] Comparative Example 1
[0049] In order to verify the key role of octadecylamine in achieving the repairable performance of the photothermally repairable superhydrophobic coating prepared by the present invention, a comparison was made with a coating prepared without adding octadecylamine.
[0050] First, octadecylamine was grafted onto the surface of carboxylated carbon nanotubes at a high temperature of 150°C by amide reaction to obtain modified carbon nanomaterials, and the dehydration condensation agent used in the amide reaction was N,N-dicyclohexylcarbodiimide; then, 4.5g E-44 epoxy resin and 4.5g polyamide curing agent were dissolved in 100g tetrahydrofuran to obtain a mixed solution, and then 9g modified carbon nanotubes were ultrasonically dispersed in 100g tetrahydrofuran to obtain a suspension; then, the above suspension and the mixed solution were mixed, ultrasonically dispersed for 15min to form a uniform suspension solution, and then the suspension solution was coated on a glass sheet by a spraying process, and the glass sheet was used as a substrate to form a coating on the surface of the glass sheet; finally, the coating was placed in an oven at 80°C for heating and curing for 2h, and then it was taken out and placed at room temperature for cooling and crystallization for 4h to obtain a repairable super-hydrophobic coating with a photothermal effect, and the repairable super-hydrophobic coating was firmly attached to the surface of the glass sheet.
[0051] The test results of the hydrophobicity, solvent stability and peeling resistance of the repairable super-hydrophobic coating are shown in Table 1, and the test results of the photothermal conversion performance and contact angle repair performance of the repairable super-hydrophobic coating are shown in Table 2.
[0052] Comparative Example 2
[0053] In order to verify the key role of octadecylamine-modified carbon nanotubes in the photothermally repairable superhydrophobic coating prepared by the present invention in improving the superhydrophobic stability and achieving repairable performance, a mixture of original carbon nanotubes and octadecylamine was used to replace the octadecylamine-modified carbon nanotubes, and the repairable superhydrophobic coating prepared under this condition was compared with that in Example 1.
[0054] First, 4.5 g of E-44 epoxy resin and 4.5 g of polyamide curing agent were dissolved in 100 g of tetrahydrofuran to obtain a mixed solution, and then 9 g of carbon nanotubes and 0.94 g of octadecylamine were ultrasonically dispersed in 100 g of tetrahydrofuran to obtain a suspension; then, the above suspension and the mixed solution were mixed, ultrasonically dispersed for 15 minutes to form a uniform suspension solution, and then the suspension solution was coated on a glass sheet by a spraying process, and the glass sheet was used as a substrate to form a coating on the surface of the glass sheet; finally, the coating was placed in an 80° C. oven for heating and curing for 2 hours, and then taken out and placed at room temperature for cooling and crystallization for 4 hours to obtain a repairable super-hydrophobic coating with a photothermal effect, and the repairable super-hydrophobic coating was firmly attached to the surface of the glass sheet.
[0055] The test results of the hydrophobicity, solvent stability and peeling resistance of the repairable super-hydrophobic coating are shown in Table 1, and the test results of the photothermal conversion performance and contact angle repair performance of the repairable super-hydrophobic coating are shown in Table 2.
[0056] Performance Testing
[0057] (1) Scanning electron microscope test
[0058] A scanning electron microscope (Zeiss sigma300, Germany) was used for morphological observation, and the accelerating voltage was set to 5 kV. Before the test, the repairable superhydrophobic coating was fixed on the sample table with conductive glue and gold-sprayed.
[0059] (2) Contact angle test
[0060] The contact angle of water droplets on the repairable super-hydrophobic coating surface was tested using a contact angle meter (SDC-200S, Dongguan Shengding Precision Instrument Co., Ltd.). The water droplet size was 5 μL, and the contact angle value was calculated as the average value at 5 locations on the repairable super-hydrophobic coating surface.
[0061] (3) Photothermal conversion performance test
[0062] In order to evaluate the photothermal conversion performance of the repairable superhydrophobic coating, a power of 2 kW / m 2 A xenon lamp light source is used to simulate sunlight and irradiate it on the surface of the repairable super-hydrophobic coating. An infrared thermal imager is used to detect and record the surface temperature of the repairable super-hydrophobic coating after 10 minutes of irradiation.
[0063] (4) Solvent stability test
[0064] In order to evaluate the solvent resistance stability of the repairable superhydrophobic coating, the repairable superhydrophobic coating was placed in n-hexane for 72 hours, then taken out and dried, and the contact angle change was measured.
[0065] (5) Tape peeling resistance test
[0066] In order to evaluate the tape peeling resistance of the repairable super-hydrophobic coating, the tape was spread flat on the surface of the repairable super-hydrophobic coating, and a 100g weight was rolled on the tape for 5 consecutive times to ensure that the tape and the sample were tightly attached, and then the tape was torn off to complete a tape destruction cycle. Subsequently, a new tape was replaced, and the tape destruction cycle was repeated 500 times, and the contact angle of the repairable super-hydrophobic coating was tested again.
[0067] (6) Repair performance test
[0068] In order to evaluate the repairability of the repairable super-hydrophobic coating, the repairable super-hydrophobic coating sample was inverted on 2500 mesh sandpaper, and a 100g weight was placed on the back of the sample repairable super-hydrophobic coating. Then the sample repairable super-hydrophobic coating was pushed to move 12cm on the sandpaper at a uniform speed to complete a sandpaper destruction cycle. Repeat this sandpaper destruction cycle 50 times, and then test the morphology and contact angle of the sample. Finally, the damaged repairable super-hydrophobic coating sample was placed in an 80°C oven and heated for 1h, placed at room temperature for 4h, and then the morphology and contact angle of the sample were tested.
[0069]
[0070] Table 1 - Test results of hydrophobicity, solvent stability and peeling resistance of repairable super hydrophobic coating
[0071]
[0072] Table 2 - Test results of the photothermal conversion performance and contact angle repair performance of the repairable superhydrophobic coating
[0073] As can be seen from the performance test of the comparative example in Table 1, compared with Example 1, the repairable super-hydrophobic coating prepared by Comparative Example 1 still has excellent super-hydrophobicity, solvent resistance stability, tape stripping resistance and photothermal conversion performance, but its surface is difficult to restore super-hydrophobicity after sandpaper abrasion damage. The flow of octadecylamine grafted with carbon tubes in the repairable super-hydrophobic coating is limited, which makes it difficult to construct enough nano-scale roughness on the surface, and the repairable super-hydrophobic coating surface contact angle is only repaired to 149 °. Although the water contact angle of the coating surface after repair only decreases by 2 ° compared with Example 1, water droplets are very easy to adhere to the coating surface, affecting the application of materials in the fields of self-cleaning, anti-icing, anti-fouling, etc. Therefore, even a contact angle change of 2 ° plays an important role in the surface properties of the coating.
[0074] Although the repairable super-hydrophobic coating prepared by comparative example 2 shows excellent super-hydrophobicity, solvent resistance stability and photothermal conversion performance, the mechanical stability and repairability of the repairable super-hydrophobic coating are greatly reduced. The repairable super-hydrophobic coating only adds movable octadecylamine molecules, but the increase in the content of waxy octadecylamine not only reduces the repairable super-hydrophobic coating mechanical properties, and octadecylamine is difficult to be fixed by the epoxy resin cross-linked network. Therefore, the repairable super-hydrophobic coating is severely damaged in physical structure after tape stripping and sandpapering, and a large amount of octadecylamine is removed from the outside and inside, and the surface contact angle is significantly reduced. At the same time, the remaining octadecylamine of the repairable super-hydrophobic coating is not enough to flow and repair its super-hydrophobicity, so the repair effect is not obvious, and the repairable super-hydrophobic coating contact angle is only restored to 148 °. Although the coating surface water contact angle after repair only decreases by 3 ° compared with Example 1, water droplets are very easy to adhere to the coating surface, affecting the application of materials in the fields of self-cleaning, anti-icing, anti-fouling, etc. In addition, since the ODA in the coating is not fixed, the surface is prone to lose its hydrophobicity due to mechanical damage even after the coating is repaired.
[0075] As can be seen from the performance test of the embodiments of Table 1 and Table 2, the repairable super-hydrophobic coating with photothermal effect obtained by Example 1-4 has excellent super-hydrophobicity, and the repairable super-hydrophobic coating still maintains super-hydrophobicity after solvent soaking 72h or tape stripping damage 500 cycles, showing excellent chemical and mechanical stability. Meanwhile, the repairable super-hydrophobic coating has good repairability, and its contact angle is less than 150 ° after sandpaper wear, but the repairable super-hydrophobic coating can restore surface super-hydrophobicity after heating. In addition, the repairable super-hydrophobic coating has significant photothermal conversion performance, and the heat can be used to promote the repair of the super-hydrophobic coating contact angle.
[0076] The repairable super-hydrophobic coating with photothermal effect of the present invention is composed of octadecylamine modified carbon nanomaterial, removable octadecylamine molecules and epoxy resin cross-linked network, and the obtained repairable super-hydrophobic coating limits the mobile octadecylamine molecules with poor stability in the epoxy resin cross-linked system, and the repairable super-hydrophobic coating as a whole shows excellent chemical and mechanical stability. Meanwhile, when the repairable super-hydrophobic coating is subjected to physical damages such as sandpaper wear, the micro-nano rough structure can be repaired by heating to make the octadecylamine melt flow and migration rearrangement of the waxy substance, thereby restoring super-hydrophobic performance. In addition, the embedding of carbon nanomaterials makes the repairable super-hydrophobic coating show excellent photothermal effect, showing extremely high value in practical applications.
[0077] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that, for a person of ordinary skill in the art, several variations and modifications can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention patent shall be subject to the attached requirements.
Claims
1. A method for preparing a repairable super-hydrophobic coating with photothermal effect, characterized in that: The following steps are included: Step S1, using an amide reaction to graft octadecylamine onto the surface of the carboxylated carbon nanomaterial at a high temperature of 150° C. to obtain a modified carbon nanomaterial; Step S2, dissolving 5 to 10 parts of epoxy resin and polyamide curing agent in 100 parts of organic solvent by mass fraction to obtain a mixed solution; Step S3, ultrasonically dispersing 2 to 10 parts of modified carbon nanomaterial and 0.15 to 1 part of octadecylamine in 100 parts of an organic solvent by mass fraction to obtain a suspension; Step S4, mixing 100 parts of the mixed solution of step S2 and 100 parts of the suspension solution of step S3 by mass fraction, and subjecting the mixture to ultrasonic dispersion treatment for 10 to 20 minutes to form a uniformly dispersed suspension solution; Step S5, coating the suspension solution on the surface of the substrate by a spraying process to form a coating on the surface of the substrate; Step S6, placing the substrate in an oven at a temperature of 60 to 100° C., heating and curing the coating coated on the surface of the substrate, taking the substrate out of the oven and placing it at room temperature, allowing the coating coated on the surface of the substrate to cool and crystallize, and forming a repairable super-hydrophobic coating with a photothermal effect on the surface of the substrate; Part of the octadecylamine in the repairable super-hydrophobic coating is grafted to the surface of the carbon nanomaterial, and part of the waxy octadecylamine is directly added to the epoxy resin cross-linking system. The combination of octadecylamine molecules with restricted mobility and octadecylamine molecules with large mobility is utilized to make the repairable super-hydrophobic coating have excellent cyclic repair stability. The repairable super-hydrophobic coating has excellent chemical / mechanical stability and repairability.
2. The method for preparing a repairable super-hydrophobic coating with photothermal effect according to claim 1, characterized in that: The surface of the repairable super-hydrophobic coating has a super-hydrophobic micro-nano rough structure, the modified carbon nanomaterial is accumulated on the surface of the repairable super-hydrophobic coating to construct a micron-sized papillary structure in the shape of a peak, and a large number of nano-sized carbon nanoparticle protrusions are distributed on the surface of the papillary structure, and the mobile octadecylamine molecules with poor stability are restricted in the epoxy resin cross-linking system. After the micro-nano rough structure on the surface of the repairable super-hydrophobic coating is damaged, the waxy octadecylamine is melted and flowed by heating and re-cooled and crystallized in the damaged area to construct roughness; After the chemical structure of the surface of the repairable super-hydrophobic coating is damaged, heating is used to accelerate the migration and rearrangement of the octadecylamine chain segments therein to reduce the surface energy of the damaged area, thereby repairing the super-hydrophobicity of the repairable super-hydrophobic coating.
3. The method for preparing a repairable super-hydrophobic coating with photothermal effect according to claim 1, characterized in that: In the step S1, a dehydration condensation agent is used in the amide reaction to graft octadecylamine onto the surface of the carboxylated carbon nanomaterial, and the dehydration condensation agent is selected from N,N-dicyclohexylcarbodiimide.
4. The method for preparing a repairable super-hydrophobic coating with photothermal effect according to claim 1, characterized in that: In the step S1, the carboxylated carbon nanomaterial is one of carboxylated carbon nanotubes and carboxylated carbon black, wherein the outer diameter of the carboxylated carbon nanotubes is greater than 20 nm, and the particle size of the carboxylated carbon black is distributed in the range of 30 to 500 nm.
5. The method for preparing a repairable super-hydrophobic coating with photothermal effect according to claim 1, characterized in that: In the step S2, the epoxy resin is an epoxy resin in an epoxy system, and the selected epoxy resin model is E-44 or E-51; and the organic solvent is one of ethanol, toluene and tetrahydrofuran.
6. The method for preparing a repairable super-hydrophobic coating with photothermal effect according to claim 1, characterized in that: The mass ratio of the epoxy resin to the polyamide curing agent is 1-2:1, the total mass of the epoxy resin and the polyamide curing agent is set as A, the input mass of the carboxylated carbon nanomaterial is 40-100wt% of A, and the input mass of the octadecylamine is 3-10wt% of A.
7. The method for preparing a repairable super-hydrophobic coating with photothermal effect according to claim 1, characterized in that: In the step S6, the coating coated on the surface of the substrate is heated and solidified for 1 to 10 hours, and the coating is cooled and crystallized for 1 to 6 hours.
8. The method for preparing a repairable super-hydrophobic coating with photothermal effect according to claim 1, characterized in that: In the step S5, the substrate comprises one of glass, iron sheet, polyethylene terephthalate film, polypropylene film and polyethylene film, and the thickness of the spray layer of the suspension solution coated on the substrate is 50 to 200 μm.
9. A repairable super-hydrophobic coating with photothermal effect, characterized in that: The repairable super-hydrophobic coating with photothermal effect is prepared by the preparation method of any one of claims 1 to 8, wherein part of the octadecylamine in the repairable super-hydrophobic coating is grafted onto the surface of the carbon nanomaterial, and part of the waxy octadecylamine is directly added to the epoxy resin cross-linking system. The combination of two types of octadecylamine molecules, one with restricted flow and one with large flow, makes the repairable super-hydrophobic coating have excellent cyclic repair stability, and the repairable super-hydrophobic coating has chemical / mechanical stability and surface repairability of the material.
10. The repairable super-hydrophobic coating with photothermal effect according to claim 9, characterized in that: The surface of the repairable super-hydrophobic coating has a super-hydrophobic micro-nano rough structure, and a micron-scale papillary structure in the shape of a mountain is constructed by accumulating modified carbon nanomaterials on the surface of the repairable super-hydrophobic coating, and a large number of nano-scale carbon nanoparticle protrusions are distributed on the surface of the papillary structure; the service life of the material is greatly extended by the movable octadecylamine molecules confined in the epoxy resin cross-linking system, and its excellent photothermal properties provide an effective way for repairability; after the micro-nano rough structure on the surface of the repairable super-hydrophobic coating is damaged, the octadecylamine is melted and flowed by heating and re-cooled and crystallized in the damaged area to construct roughness; after the chemical structure of the surface of the repairable super-hydrophobic coating is damaged, the migration and rearrangement of the octadecylamine segments are accelerated by heating to reduce the surface energy of the damaged area, so as to achieve the repair of the super-hydrophobicity of the repairable super-hydrophobic coating.
Citation Information
Patent Citations
A self-healing superhydrophobic drag-reducing elastomer film and its preparation method
CN107459668B
A method for preparing a graphene-based self-healing superhydrophobic coating
CN108641421B
A self-healing superhydrophobic antireflective coating and coating
CN116676002B
Cited By
Aluminum alloy surface double-response self-repairing super-hydrophobic coating and preparation method thereof
CN120775471A